Multichannel intraluminal impedance‐pH and psychometric properties in gastroesophageal reflux: systematic review - Emília Silva Gonçalves; Maíra Seabra de Assumpção; Maria Fátima Correa Pimenta Servidoni; Elizete Aparecida Lomazi; José Dirceu Ribeiro (Brazilian Society of Pediatrics, 2020)
Objective: Systematically assess studies that have analyzed the psychometric properties of multichannel intraluminal impedance‐pH for the diagnosis of gastroesophageal reflux. Systematically verify studies that have analyzed the psychometric properties of multichannel intraluminal impedance‐pH regarding the diagnosis of gastroesophageal reflux disease in pediatric patients. Methods: Systematic review considering specific descriptors (children and adolescents, gastroesophageal reflux disease and multichannel intraluminal impedance‐pH) and their synonyms. The systematic search was carried out in the MEDLINE/Ovid, Scopus, and Embase databases, considering the period from October 2017 to December 2018. This review was conducted according to the Preferred Reporting Items for Systematic Reviews and Meta‐Analyses (PRISMA), which was used for study selection. The psychometric properties described in the studies were: sensitivity, specificity, accuracy, and reproducibility. Results: Sensitivity was discussed in most studies, with a result of more than 70% in four of them. Specificity was assessed only in conjunction with sensitivity, with values from 23% to 25% in two studies, and it reached 80% in a single study. Accuracy was assessed higher than 76% in one of the selected articles. The methodological quality of the studies demonstrated low risk of bias, and there was no significant concern related to applicability of the studies. Conclusions: According to the selected studies, multichannel intraluminal impedance‐pH was considered a safe and effective tool, presenting higher sensitivity values than pHmetry regarding the diagnosis of gastroesophageal reflux disease. Resumo: Objetivo: Avaliar sistematicamente estudos que analisaram propriedades psicométricas da impedância intraluminal multicanal associada à pHmetria (IIM‐pH) no diagnóstico de refluxo gastroesofágico. Verificar sistematicamente estudos que analisaram as propriedades psicométricas de impedância intraluminal multicanal associada à pHmetria em relação ao diagnóstico da doença do refluxo gastroesofágico em pacientes pediátricos. Métodos: Revisão sistemática que considerou descritores específicos (crianças e adolescentes, doença do refluxo gastroesofágico e impedância intraluminal multicanal associada à pHmetria) e seus sinônimos. A busca sistemática foi realizada nas bases de dados Medline/Ovid, Scopus e Embase e considerou o período de outubro de 2017 a dezembro de 2018. Esta revisão foi realizada de acordo com o checklist Preferred Reporting Items for Systematic Reviews and Meta‐Analyses (Prisma), usado para seleção de estudos. As propriedades psicométricas descritas nos estudos foram: sensibilidade, especificidade, acurácia e reprodutibilidade. Resultados: A sensibilidade foi discutida na maioria dos estudos, com um resultado de mais de 70% em quatro deles. A especificidade foi avaliada apenas em conjunto com a sensibilidade, com valores em torno de 23 a 25% em dois estudos, e alcançou 80% em um único estudo. A acurácia foi avaliada em mais de 76% em um dos artigos selecionados. A qualidade metodológica dos estudos demonstrou baixo risco de viés e nenhuma consideração significativa relacionada à aplicabilidade dos estudos. Conclusões: De acordo com os estudos selecionados, a impedância intraluminal multicanal associada à pHmetria foi considerada uma ferramenta segura e eficaz, apresentou valores de sensibilidade superiores à pHmetria no diagnóstico da doença do refluxo gastroesofágico.